Technical and Economical Evaluation of Oleum Elimination from Sulphuric Acid Unit of Petrochemical Industries - ATABI, FARIDEH; ATAEI*, ABTIN; MOHAMMADI, RAHELE (Asian Journal of Chemistry, 2009)
In present study, one of the sulphuric acid production units in Iran was investigated. By utilizing HYSYS v3.1 software the condition of this unit was simulated. On the basis of the simulation results analysis, a patent was considered to study the new method on it to reach a minimum amount of oleum generation. Therefore, generated oleum was reduced from 0.917 to 0.498 m3/h which was measured from the stack of investigated unit. To gain the extra amount of oleum produced before the absorption tower, another method was considered. Therefore, liquid oleum was achieved ca. 8.376 m3/h which converted to initial raw materials, ca. 7.129 m3/h SO3 gas and 0.386 m3/h liquid H2SO4. To ensure that the patent is economically cost-effective, economical indices and sensitivity analysis was considered by utilizing COMFAR III software. The econo-mical results shows internal rate of return 19.49 %, payback period 5.5 years and net present value 31,985,781 Euro. Considering external costs, the mentioned values would be 74 %, 2.3 year and 149,016 Euro. Consequently, emission of oleum from this sulphuric acid production unit would be cost-effective with or without considering external costs.